Implementasi Pengukuran Kinerja Model Malcolm Baldrige untuk Kinerja Unggul dalam Meningkatkan Keunggulan Bersaing di PT Pos Indonesia - Hesti Sugesti; Angga Dewi Anggraeni (Sosio e-Kons, 2020)
Problems faced by PT. Pos Indonesia is the number of private competitors engaged in logistics, making it difficult to compete in the industry. By implementing company performance measurement using the Malcolm Balridge Performance Excellence model, it is expected that PT. Pos Indonesia can find out its advantages and can improve it. Based on the results of research to 88 respondents using quantitative verification methods, obtained an overview of the company's performance is in the very good category but the measurement of company performance has not been fully measured using the Malcolm Balridge method, and a picture of competitive advantage in either category. From the data analysis test results obtained by the company's performance with the Malcolm Balridge model has a positive and significant effect on competitive advantage at PT. Pos Indonesia.